2018
DOI: 10.3389/fnins.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Based Identification of SIRT5 and Protein Kinase C Epsilon Regulated Pathways in Brain

Abstract: The role of Sirtuins in brain function is emerging, yet little is known about SIRT5 in this domain. Our previous work demonstrates that protein kinase C epsilon (PKCε)-induced protection from focal ischemia is lost in SIRT5−/− mice. Thus, metabolic regulation by SIRT5 contributes significantly to ischemic tolerance. The aim of this study was to identify the SIRT5-regulated metabolic pathways in the brain and determine which of those pathways are linked to PKCε. Our results show SIRT5 is primarily expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
0
18
1
1
Order By: Relevance
“…In addition, both levels of mitochondrial respiration and lysine desuccinylation activity were increased on ΨεRACK treatment. [ 51 58 ] This is contrary to what was observed in heart and MEFs, where cellular respiration was decreased in the presence of SIRT5. SIRT5 may contribute to the differences in mitochondrial respiration between tissues through its regulation of several mitochondrial metabolic proteins through lysine desuccinylation.…”
Section: Sirt5 Regulates Several Metabolic Processes During Ischemiacontrasting
confidence: 67%
See 2 more Smart Citations
“…In addition, both levels of mitochondrial respiration and lysine desuccinylation activity were increased on ΨεRACK treatment. [ 51 58 ] This is contrary to what was observed in heart and MEFs, where cellular respiration was decreased in the presence of SIRT5. SIRT5 may contribute to the differences in mitochondrial respiration between tissues through its regulation of several mitochondrial metabolic proteins through lysine desuccinylation.…”
Section: Sirt5 Regulates Several Metabolic Processes During Ischemiacontrasting
confidence: 67%
“…[ 50 59 60 ] Metabolomics studies have also indicated that SIRT5 can regulate central metabolic pathways in the brain that link its activity to ischemic tolerance. [ 51 ] These findings suggest a neuroprotective role for SIRT5 in cerebral ischemia.…”
Section: Sirt5 Regulates Several Metabolic Processes During Ischemiamentioning
confidence: 94%
See 1 more Smart Citation
“…This reveals that increased sirt5 activity has a positive impact on age and blood glucose. Studies have identified that sirt5 is involved in ketone body synthesis, TCA cycle, β-oxidation of fatty-acids, amino acid catabolism, glycolysis and ATP synthesis [45,46]. Recently, a study involved two pancreatic β-cell lines MIN6 and INS-1 has shown that inhibition of Sirt5 promoted proliferation of pancreatic β-cells and secretion of insulin [44].…”
Section: Sirt5mentioning
confidence: 99%
“…There is a lack of information on the effect of SIRTs in the regulation of EAAT2 expression. A recent metabolomics study using SIRT5 knockout mice model showed dysregulation of glutamate levels in brain cortex and reduced expression of EAAT2 at mRNA level (Koronowski et al, 2018).…”
Section: Role Of Hdacs and Sirtuins In Eaat2 Expressionmentioning
confidence: 99%